2018
DOI: 10.1002/ijgo.12539
|View full text |Cite
|
Sign up to set email alerts
|

Parental acceptance of HPV vaccines in Chiang Mai, Thailand

Abstract: Parental beliefs have an important role in their acceptance to vaccinate their daughters. These potentially modifiable beliefs offer strategies for future interventions designed to increase uptake for future HPV vaccination campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Parental beliefs about severity of HPV infection or cervical cancer, and beliefs about benefits of vaccination in general were indirect positive predictors of intention to vaccinate. Studies among parents in another region of India [18], China [44], Indonesia [19], and Thailand [20,23,24] also showed a positive relationship between attitudes about benefits of HPV vaccine (e.g. effective, prevent HPV infection and cervical cancer, affordable) and parents' intention to vaccinate with HPV vaccine .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Parental beliefs about severity of HPV infection or cervical cancer, and beliefs about benefits of vaccination in general were indirect positive predictors of intention to vaccinate. Studies among parents in another region of India [18], China [44], Indonesia [19], and Thailand [20,23,24] also showed a positive relationship between attitudes about benefits of HPV vaccine (e.g. effective, prevent HPV infection and cervical cancer, affordable) and parents' intention to vaccinate with HPV vaccine .…”
Section: Discussionmentioning
confidence: 93%
“…side effects, high cost, less efficacious, promote sexual promiscuity) in India [16][17][18], Indonesia [19], Thailand [20], Japan [21] and Malaysia [22]. Studies also showed a decreased intention to vaccinate daughters with HPV vaccine among parents who had poor perception of susceptibility to HPV infection or cervical cancer, and severity of the disease in India [18], Indonesia [19], Japan [21] and Thailand [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Parental beliefs about severity of HPV infection or cervical cancer, and beliefs about benefits of vaccination in general were indirect positive predictors of intention-to-vaccinate. Studies among parents in another region of India , Hong Kong, China (Wang et al, 2017), Indonesia and Thailand Grandah et al, 2018;Juntasopeepun & Thana, 2018) also also showed a positive relationship between attitudes about benefits of HPV vaccine (e.g. effective, prevent HPV infection and cervical cancer, affordable) and parents' intention-to-vaccinate with HPV vaccine.…”
Section: Discussionmentioning
confidence: 87%
“…Thailand (84%-85%) Juntasopeepun et al, 2018). Even in Mysore district, the intention to HPV vaccination rate was greater among parents who were living in the rural (79.9%) than those living in the urban (71.1%) area .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation